Seroprevalence of HTLV‐1 and HTLV‐2 amongst mothers and children in Malawi within the context of a systematic review and meta‐analysis of HTLV seroprevalence in Africa. Issue 3 (3rd February 2016) - Fox, James M.; Mutalima, Nora; Molyneux, Elizabeth; Carpenter, Lucy M.; Taylor, Graham P.; Bland, Martin; Newton, Robert; Martin, Fabiola
Abstract: Objectives: Human T‐lymphotropic virus (HTLV)‐1 causes T‐cell leukaemia and myelopathy. Together with HTLV‐2, it is endemic in some African nations. Seroprevalence data from Malawi are scarce, with no reports on associated disease incidence. HTLV seroprevalence and type were tested in 418 healthy mothers from Malawi. In addition, we tested the sera of 534 children to investigate mother‐to‐child transmission. To provide context, we conducted a systematic review and meta‐analysis of HTLV seroprevalence in African women and children. Methods: Stored samples from a previous childhood cancer and BBV study were analysed. ELISA was used for HTLV screening followed by immunoblot for confirmation and typing. Standard methods were used for the systematic review. Results: HTLV seroprevalence was 2.6% (11/418) in mothers and 2.2% (12/534) in children. Three mothers carried HTLV‐1 alone, seven had HTLV‐2 and one was dually infected. Three children carried HTLV‐1 alone, seven had HTLV‐2 and two were dually infected. Only two corresponding mothers of the 12 HTLV‐positive children were HTLV positive. The systematic review included 66 studies of women and 13 of children conducted in 25 African countries. Seroprevalence of HTLV‐1 varied from 0 to 17% and of HTLV‐2 from 0 to 4%. Conclusions: In contrast to findings from other studies in Africa, the seroprevalence of HTLV‐2 was higher than that of HTLV‐1 in Malawi and one of the highest for the African region. The lack of mother–child concordance suggests alternative sources of infection among children. Our data and analyses contribute to HTLV prevalence mapping in Africa.